Wicklowia phuketensis (Wicklowiaceae, Pleosporales), a novel freshwater taxon from Thailand - Mark S. Calabon (2020)
Copyright © 2020 Magnolia Press An investigation of aquatic fungi in Thailand resulted in the collection and isolation of a new species of Wicklowia (Wicklowiaceae) from submerged wood. Wicklowia phuketensis sp. nov. differs from known species in morphology and multigene phylogenetic analyses. Both W. submersa and W. phuketensis lack appendages at both ends, while W. aquatica has basal appendages. Wicklowia phuketensis differs from other species in the dimensions of the ascomata, asci and ascospores. The combined LSU and SSU sequence data placed the new species within Wicklowiaceae.